Dinamika Pembelajaran IPS pada Kurikulum Berbasis Cinta di MI - Frika Fatimah Zahra; Nabila Dwi Az-zahra; Vicca Zahra Ferisa; Jamilah Badriyah (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to identify and describe the teaching process of Social Studies (IPS) in third-grade elementary school through direct observation. The method used involved an observation sheet designed in accordance with the research objectives to collect information on teacher and student activities, the teaching approach applied, and the use of teaching materials. The research findings revealed that although students were less actively involved, the lecture technique was still the main method in teaching Social Studies in third-grade elementary school. However, the practice of interactive instructional strategies, such as group discussions, the effective use of suitable instructional media is believed to enhance learners’ participation and foster greater motivation in the learning process. Furthermore, a harmonious interaction between educators and students also plays a role in establishing a supportive and comfortable learning atmosphere. The main obstacles include limited teaching materials and limited learning time. This study concludes that teaching Social Studies at the elementary school level needs to utilize a variety of interesting techniques and teaching materials to increase learning efficiency and foster student interest. These results provide useful empirical data as a basis for evaluating and improving Social Studies teaching in third-grade elementary school, so that it is more appropriate to the characteristics and needs of students.